Evaluasi Pelatihan Rencana Pemulihan Usaha Dalam Program Muhammadiyah Disaster Managemen Center - Fery Fery; Muhamad Dasril (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
This study aims to determine aspects of satisfaction and increase knowledge of participants in participating in the Business Recovery Plan Training (RPU) in the Micro and Tsunami Recovery Program for the Disasters of the Earthquake and Tsunami conducted by the Muhammadiyah Disaster Management Center (MDMC) in collaboration with Solidar Suisse. This type of research is a qualitative descriptive, data collection methods of observation studies, interviews, documentation, and data analysis techniques through interpretive analysis approach techniques. The results of the study showed that most of the Sirenja people who participated in the Business Recovery Plan Training (RPU) were satisfied and had understood about the preparation of the RPU on good performance. But it is still low in the practice of preparing RPU.